Acid mine drainage in abandoned mine - Nur Athirah, Mohamad Basir; Abdul Aziz, Mohd Azoddein; Nur Anati, Azmi (Universiti Malaysia Pahang, 2018)
Acid mine drainage (AMD) in abandoned mining operations related oxidation of sulfide mineral affording an acidic solution that contains toxic metal ions. Hence acidic water that flow into the stream had potential health risks to both aquatic life and residents in the vicinity of the mine. Study will be conduct to investigate water quality and AMD characteristics which are pH value of the stream or discharge area, mineral composition in the rock and neutralization value of the rock in AMD mining area. Result shows that pH value of water in Kg. Aur, Chini and Sg. Lembing are acidic with value of 2.81, 4.16 and 3.60 respectively. Maximum concentrations of heavy metals in the study area are: Pb (0.2 mg/L), Cd (0.05 mg/L), Zn (5.1 mg/L), Cu (5.2 mg/L), Mn (10.9 mg/L), Cr (0.2 mg/L), Ni (0.2 mg/L), As (0.005 mg/L) and Fe (202.69 mg/L). Prediction of acid formation using acid-base calculations from all samples shows high potential acid production between 22.84-2500.16 kg CaCO₃/tonne. The ratio of neutralization (NP) with acid potential (APP) shows a very low value (ratio < 1) Sg. Lembing (0.02), Chini (0.08) and Kg. Aur (0.81). The potential value of this acid production exceeds the neutralization potential value in the mine. It is inferred that AMD is being produced in the Sg Lembing, Cini and Kg Aur. It is recommended that an Environmental Impact Assessment of AMD must be carried out before the mine is reopened.